IMPLEMENTASI NILAI-NILAI AGAMA HINDU TERHADAP PENYELESAIAN TINDAK PIDANA ADAT DI BALI - Rizky Sitraputra, Putu (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 4 (2015), 2015)
Research on the implementation of the values ??of Hinduism to the completion of customary criminal acts in Bali. Most of the population adheres to Balinese Hinduism, daily activities always adhered to the concept of Tri Hita Karana, which in turn is continuously executed. Human relationships with others based on the nature of mind that is communal or kinship based pleh soul. To set the level of a good life together customs regulations grow and develop with imbued the values ??of Hinduism. Customary rules and formulate actions that are required, allowed or prohibited as village members must perform the obligations to the village, prohibition for people who are dirty entering the sacred area. Incestuous copulation cases which occurred in Bali only charged criminal under national law alone. Actually, should also be reviewed from the local community sector appropriate sanctions in order to satisfy the sense of justice. The values ??of Hinduism derived from Hindu law aims to balance the natural result of gross misconduct perpetrator intercourse, judicial practice provides an opportunity for the judge to impose sanctions customary in accordance with Law number 48 of 2009, which states the court in addition must contain reasons and grounds of this decision, as well must contain a specific article of the source of unwritten law that formed the basis for the judge. Hindu religious values ??in the practice of judicial consideration by the judge and the efforts made in the traditional village of indigenous criminal offense .. The method used is empirical research methods to conduct field research in which cases occur. The procedure for sampling used is purposive sampling. The data is processed and analyzed qualitatively. The results showed that the judicial practice in cases of promiscuity in state court Amlapura not consider matters relating to the values ??of Hinduism. Efforts made in the traditional village settlement gamia gamana customs offense is to apply awig awig traditional village or Paruman each indigenous villages.
Keywords: Customs; Hindu religion; Pakraman Village